Strategi Pengembangan Sumber Daya Manusia Dalam Meningkatkan Kinerja Karyawan - Miftahudin Miftahudin (Tadbir: Jurnal Manajemen Dakwah, 2018)
The purpose of this research is to find out how the process of human resource training conducted by the Synergy Foundation, how the process of human resource education conducted by the Synergy Foundation, how the career development process is carried out by the Sinergi Foundation in an effort to improve the quality of employee performance. The method used in this research is descriptive method, using a qualitative approach. Based on the results of the study, the training process carried out was based on the results of the annual Sinergi Foundation evaluation. Strategies carried out in training by on the job, and recommending their employees to attend training outside the institution. Furthermore, the process of employee education is more focused on employee theoretical understanding. Straregi is used by conducting education within the institution and sending its employees to study outside. Development of the quality and quantity of employees, the leadership has policies and directives for all employees in the structural to have a new concept with the aim that each department has innovation about the development of its department.